Multi-compartment Microfluidic Device Geometry and Covalently Bound Poly-D-Lysine Influence Neuronal Maturation - Kamande, Joyce W.; Nagendran, Tharkika; Harris, Joseph; Taylor, Anne Marion (Frontiers in Bioengineering and Biotechnology, 2019)
Multi-compartment microfluidic devices have become valuable tools for experimental neuroscientists, improving the organization of neurons and access to their distinct subcellular microenvironments for measurements and manipulations. While murine neurons are extensively used within these devices, there is a growing need to culture and maintain human neurons differentiated from stem cells within multi-compartment devices. Human neuron cultures have different metabolic demands and require longer culture times to achieve synaptic maturation. We tested different channel heights (100 µm, 400 µm, and open) to determine whether greater exposure to media for nutrient exchange might improve long-term growth of NIH-approved H9 embryonic stem cells differentiated into glutamatergic neurons. Our data showed an opposite result with both closed channel configurations having greater synaptic maturation compared to the open compartment configuration. These data suggest that restricted microenvironments surrounding neurons improve growth and maturation of neurons. We next tested whether covalently bound poly-D-lysine (PDL) might improve growth and maturation of these neurons as somata tend to cluster together on PDL adsorbed surfaces after long culture periods (>30 days). We found that covalently bound PDL greatly improved the differentiation and maturation of stem cell-derived neurons within the devices. Lastly, experimental paradigms using the multi-compartment platform show that axons of hSC-neurons intrinsically regenerate in the absence of inhibitory cues and that isolated axons form presynaptic terminals when presented with synaptic targets.